THE EFFECT OF KAFFIR LIME PEEL EXTRACT (Citrus hystrix) ON SPATIAL MEMORY OF MICE WITH DEMENTIA USING MORRIS WATER MAZE - Florentina Anindita Christiyanto; Endang Mahati; Noor Wijayahadi; Yora Nindita (Jurnal Kedokteran Diponegoro, 2023)
Background: Antioxidants are a group of chemicals that protect biological systems against the potential harmful effects of oxidation processes or its reactions. Kaffir lime peel (Citrus hystrix) contains various potential antioxidants substances those are able to protect neurons from free radical-induced damage. Objective: To evaluate the effect of kaffir lime peel extract (Citrus hystrix) on the spatial memory of mice induced by Scopolamine (SCM). Methods: This research was a true experimental study with a post-test-only controlled group design. Thirty mice were randomly divided into 5 groups. SCM was injected intraperitoneally on day 1-7 and kaffir lime peel extract was given orally on day 2-7, the spatial memory testing of mice using Morris Water Maze on day 8. Data analysis used One-Way ANOVA test (α = 0.05) and continued with Post Hoc LSD test (α = 0.05). Results: The mean spatial memory of K+, K-, P1, P2,P3 were 16,33 ± 7,42; 70,00 ± 32,24; 25,66 ± 24,43; 23,00 ± 19,39; 25,00 ± 19,50 seconds respectively. There were significant differences in spatial memory in P1, P2, dan P3 to the negative control group, but there is no significant differences between treatment grups. Conclusion: Kaffir lime peel extract (Citrus hystrix) can improve the spatial memory of scopolamine-induced dementia (SCM) mice. There is no dose effect relationship between the treatment groups